Problematika Dalam Menghafal Al-Qur’an Bagi Siswa Kelas X MAS Al-Fath Langkat - Maya Azhan, Muhizar Muchtar, Muamar Al Qadri (Pusdikra Publishing, 2023)
This research is a field research (field research), with a qualitative approach, the subjects used in this study are students keals X MAS Al Fath Langkat and also ustadz and ustadzah tahfidz house MAS Al Fath Langkat became informants in the study. Data collection techniques used in this study are observation, interviews, and documentation. From the results of the study it is known that the implementation of the Qur'an memorization program in class X MAS Al Fath Langkat is carried out on Monday to Friday after school starts at 14:00 - Before Asr. The implementation of the tahfidz program in class X MAS Al Fath Langkat begins with reading first and depositing the reading then memorizing and depositing their respective memorization. Then after the implementation of this activity will be evaluated by the tahfidz coach every 6 months to determine the improvement of the memorization ability of each student. Problems of class X students of MAS Al-Fath Langkat in memorizing the Qur'an include the difficulty of students dividing school and cottage time, the emergence of laziness, lack of muroja'ah, difficulty dividing time, there are verses that are difficult to memorize and a less conducive environment. The solution applied by students of class X MAS Al Fath Langkat in overcoming the problems they face is divided into several parts. The solution to overcoming the problem of time sharing is by increasing school learning hours and students are required to be able to manage time so that they can manage between doing schoolwork and memorizing, then to overcome the problem of laziness the solution is that students must return to their intention and also the teacher must continue to provide motivation and reward for students who memorize. Furthermore, to overcome the problem of muroja'ah, the teacher always guides students for 15 minutes before starting the lesson to repeat their memorization. To overcome verses that are difficult to memorize, the solution is that students must learn more extra in understanding the verse and determine the right method in memorizing such as dividing the verse into several parts before memorizing or writing back the verse so that it is easy to remember. To overcome the problem of a less conducive location, teachers and students in the implementation should not watch in the classroom, it should be done in a quiet and quiet place so that students can more easily concentrate on memorizing.